PENGARUH TINGKAT SUKU BUNGA PINJAMAN DAN VOLUME PINJAMAN TERHADAP RETURN ON ASSETS (ROA) PADA PT. BPR MITRA DAYA MANDIRI PERIODE TAHUN 2008 SAMPAI 2010 - Fauzi, Rizki Ahmad (Jurnal Ilmiah Binaniaga, 2012)
Bank as a business organization has become a tool and a means of supporting the liquidity of the business , as a consequence, banks are required to become a business organisasasi proper and prudent in the distribution of funds in the form of credit . It has been recognized correctly by the community because the business function other than as a financial intermediary bank , also the agent of development that have an obligation to support the equitable distribution of national development efforts . Thus the function of banking business as the source of funds and lending function must be balanced in order to create proper banking .Interest Rate Loans positive and significant impact on Return on Assets ( ROA ) . This suggests that the higher the Loan Interest Rate Return on Assets ( ROA ) acquired banks will be even greater because of the higher Interest Rate Loans , the greater the income received from the debtor banks because the rate of return on bank loans . The greater the bank's profitability ( ROA ) obtained by the bank , which means the financial performance has improved or increasedVolume of Loans positive and significant impact on Return on Assets ( ROA ) . This suggests that the greater the volume of loans then Return on Assets ( ROA ) acquired banks will be even greater because of the greater volume of loans , the higher the income received from the debtor banks because the rate of return on bank loans . The greater the bank's profitability ( ROA ) obtained by the bank , which means the financial performance has improved or increased . Adjusted R Square value of 0.121 indicates that 12.1 % of the dependent variable of financial performance proxied by ROA can be explained by the two independent variables , namely interest rates and credit and loan volumes , while the remaining 87.9 % is explained by other factors outside the regression model analyzed . This study did not escape from the limitations . Limitations contained in this research can be seen from the value of Adjusted R Square which can only explain 12.1 % or a fraction of the variance of dependent variable , while 87.9 % is influenced by other factors that are not included in the model so that there are many variables that influence but not included in this model . Given the tremendous influence of the independent variable on the dependent variable , it is suggested the need for caution in generalizing the results of this study . Based on the results of statistical tests , the three variables that partially have a significant effect , Interest Rate Loans has the highest influence on ROA , as evidenced by the Beta value of the variable size of the company showed a number greater volume of loans amounting to 1,050 .Keywords : loan rates , loan volume , return on assets